Hippocampal-related memory deficits and histological damage induced by neonatal ionizing radiation exposure: Role of oxidative status - Cáceres, Lucila Guadalupe (2009)
Ionizing radiations induce oxidative stress on target tissues, mainly through the generation of reactive oxygen species (ROS). However, there are few data available on the behavioral effects of moderate doses of ionizing radiation. The aim of the present work was to evaluate the performance of adult rats irradiated at birth in different hippocampal-dependent behavioral tasks and to establish a relationship with the oxidative status and histological changes in rat hippocampus (Hip). Male Wistar rats were irradiated with 5 Gy of X rays between 24 and 48 h after birth. Thirty days later, rats were subjected to open field, object recognition and inhibitory avoidance tasks. In addition, oxidative status markers as well as protein kinase C (PKC) activity and histological changes were assessed in control and irradiated Hip. Results show an impairment in recognition and habituation memories in 30-day-old animals exposed to neonatal ionizing radiation, both at short- (ST) and at long-term (LT), whereas an improvement in associative memory was observed at ST. In addition, histological alterations were observed in irradiated Hip. Although an increase in ROS levels and PKC activity were found in irradiated Hip, no changes in the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) were observed. Taken together, our results support the hypothesis that an increased PKC activity, induced by neonatal ionizing radiation on rat Hip, could play a role in the generation of an imbalance between ROS levels and antioxidant systems and might underlie radiation-induced hippocampal histological damage as well as the Hip-dependent behavioral changes found in irradiated rats.